Siyasi Kutuplaşmanın Marka İmaj Ve İtibarlarına Etkisi: Türkiye’De Tüketicinin Yahudilikle İlişkilendirdiği Markalara Bakışı Üzerine Bir Eleştiri - Kırgız, Ayça C. (The Turkish Online Journal of Design Art and Communication, 2015)
The main reason why the businesses want to create psychological differences rather than physical or functional differences is the existence of many companies providing similar products and services in the market. Provision of products and services exceeding the requests and needs of clientele, similarity of each and every one of them with each other both physically and functionally, the requirement of selling them due to inventory and other different costs have made it compulsory to emphasize on establishing psychological bonds between such products, and the consumers. The brands, over time, have begun to be employed with symbolic purposes in addition to their physical or functional properties by differentiating from each other with an eye to gain competitive advantage and establish psychological bonds with consumers. The consumers receive help from the brands they consume in creating social identity. In this sense, brands act as a kind of social passport. In our day it is not possible to examine brands separately from their psychological, political, social and cultural dimensions. To understand the variables of brands such as class and status in terms of sociology; groups and ethnic origin in terms of politics; motivations and habits in terms of psychology and pleasure and meaning in terms of anthropology more than the price and functions of brands plays an important role in creating the image and reputation of the desired brand. For, the consumers also consume the meanings offered by the brands in addition to brands themselves. In this study, it is researched how brands create an impact on the brand image and reputation by the effect of ethnic and religious origins, the political developments in the world and political and social structures in the society they exist. As such, the impact of the Israel and Jewish originated global brands- due to the Israel’s being the leading actor of the Palestinian-Israeli war- on Turkish consumers is researched and discussed.
Keywords: Marka İmajı; Marka İtibari; İsrail ve Yahudi Menşeili Markalar; Brand İmage; Brand Reputation; Israel and Jewish Originated Global Brands